2016
DOI: 10.1111/1556-4029.13326
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Intoxication with α‐PVP, a Synthetic Cathinone Derivative

Abstract: This study presents the fatal case of a young man who was admitted to the ICAU due to sudden cardiac arrest. An interview revealed that the patient had taken some unspecified crystals. From the moment of admission, his condition deteriorated dramatically as a result of increasing circulatory insufficiency. After a few hours, sudden cardiac arrest occurred again and the patient was pronounced dead. In the course of a medicolegal autopsy, samples of biological material were preserved for toxicology tests and his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(12 citation statements)
references
References 21 publications
(22 reference statements)
1
10
0
1
Order By: Relevance
“…Hereditary myocardial ion channel disorders such as LQTS and Brugada syndrome are known to cause lethal cardiac arrhythmias, and in recent years, it has become apparent that certain drugs can induce acquired LQTS 8 , 10 , 11 , 16 , 17 , 20 , 21 . Antipsychotic drugs in particular have been shown to lead to LQTS by blocking myocardial K + channels, and KCNQ1 mutations have been detected significantly more frequently among patients having died during use of such drugs 8 , 10 , 11 , 19 , 21 23 . We therefore hypothesized that asymptomatic individuals possessing LQT gene polymorphisms associated with K + channel dysfunction face increased risk of serious cardiac arrhythmia induced by illegal drug use.…”
Section: Discussionmentioning
confidence: 99%
“…Hereditary myocardial ion channel disorders such as LQTS and Brugada syndrome are known to cause lethal cardiac arrhythmias, and in recent years, it has become apparent that certain drugs can induce acquired LQTS 8 , 10 , 11 , 16 , 17 , 20 , 21 . Antipsychotic drugs in particular have been shown to lead to LQTS by blocking myocardial K + channels, and KCNQ1 mutations have been detected significantly more frequently among patients having died during use of such drugs 8 , 10 , 11 , 19 , 21 23 . We therefore hypothesized that asymptomatic individuals possessing LQT gene polymorphisms associated with K + channel dysfunction face increased risk of serious cardiac arrhythmia induced by illegal drug use.…”
Section: Discussionmentioning
confidence: 99%
“…In 23 of these cases, α-PVP was the cause or a contributing cause of death, and in 5 of these cases, it was the only drug detected. In a sudden death during restraint of an individual with symptoms of excited delirium after self-administration of α-PVP, the PM blood concentration was 0.41 mg/L [26], whereas in two other fatal α-PVP poisonings, the concentrations were 0.17 mg/L and 0.85 mg/L [27,28]. A US study has reported three fatal α-PVP poisonings with a PM blood concentration of 0.033, 0.054, and > 20 mg/L, the last one occurring in custody after the victim swallowed the drug [29].…”
Section: Discussionmentioning
confidence: 96%
“…60 Yirmi sekiz yaşında bir erkek vakada; ölüm kardiyak arrest sonucu meydana gelmiş olup, kanda α-PVP ve pentedron saptanmıştır. 61 α-PVP ile ilişkili üç ölüm vakasının yaşları sırasıyla 31, 35 ve 51 olup, toksikolojik analiz sonuçlarına göre kanda 0,29, 0,52 ve 0,1 mg/L konsantrasyonlarda madde saptanmıştır. En genç olan vakanın saldırgan ve paranoyak davranışlar gösterdikten sonra, güvenlikle girdiği silahlı çatışma sırasında ateşli silah yaralanmasından öldüğü bildirilmiştir.…”
Section: İntoksi̇kasyon Ve öLümlerunclassified